Complete chloroplast genome sequence of Swertia mileensis (Gentianaceae): a medicinal species endemic to China. Issue 2 (3rd July 2019) - Yang, Cong-Wei; Liu, Ying-Ying; Zhang, Ying-Min; Ma, Xiao-Hui; Qian, Zi-Gang; Li, Guo-Dong
Abstract: Swertia mileensis is an important medicinal plant endemic to South-east Yunnan, China, which has been widely used to treat icteric hepatitis. The complete chloroplast genome sequence of S. mileensis is presented in this study, the total size is 153, 015 bp in length with a typical quadripartite structure including a pair of inverted repeat (IRs, 25, 786 bp) regions separated by a large single copy (LSC, 83, 048 bp) region and a small single copy (SSC, 18, 395 bp) region. The overall GC content of it is 38.2%. The cp genome has 134 annotated genes, including 85 protein-coding genes, 37 tRNA genes and 8 rRNA genes. Among these genes, nine genes have one intron and two genes contain two introns. The phylogenetic tree based on 16 complete plastomes of support close relationships among two species of Swertia with 100% bootstrap value.